Developing a Framework of Measuring Course Summative Assessment for A Big Classroom (S/O 13870) - Ahmad Mustaffa, Nurakmal; Zulkifli, Malina; Indra@ Murat, Rusdi (UUM, 2020)
This research describes a framework for providing a quantitative measurement of a Course Learning Outcome (CLO) in assessing students’ achievement at higher learning institutions for a course taught by many lecturers in a large class (50 students or more). Different views on assessment methods and measurements and the diversity of students’ ability in achieving each CLO may result in difficulty in providing a standard measurement assessment in the Outcome-Based Education (OBE) system. A study was conducted on a service course of Elementary Statistics in Universiti Utara Malaysia.CLOs’ scores were calculated and analyzed on the results of 110 students in one semester using three different methods: Average, Threshold and Performance Vector. The achievement of CLOs is then grouped and tabulated in a Course Performance Report for assessing students’ performance in the course. From the study, the overall result showed that all CLOs were achieved in all three methods used. However, detailed outcomes from each method suggest a different pattern of the CLOs' attainment. From the students’ achievement perspective, the results serve as an indicator to identify which CLO failed to achieved while from the course assessment design perspective, it is an indicator to assess the consistency of various assessment tools in measuring CLOs.